Pelvic Pain - Infections - Villegas Echeverri, Juan (2015)
Surgical treatment of vulvar pain and dyspareunia. Practical approach of dysmenorrhea in adolescents. Vulvovaginitis in the infant and adolescent. Office rapid tests for the diagnosis of cervical and vaginal infections.